Rekam Medis Elektronik dalam Menunjang Efektivitas Kerja di RS Advent Medan - Nayanda Privanezsa Hao; Pomarida Simbolon (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Electronic medical records (EMR) are the use of information technology devices for collecting, storing, processing and accessing data stored in patient medical records in a database management system that collects various sources of medical data. The purpose of analyzing electronic medical records in Supporting work effectiveness at Medan Adventist Hospital, the descriptive design research design to determine the picture in supporting effectiveness, the sample of EMR officers with quota sampling techniques, the number of samples are 30, the research instrument using a questionnaire, the data analysis used is univariate, the EMR research obtain results that good electronic medical records are 26 people (86.7%) and less than 4 people (13.3%), and the work effectiveness research obtain the results that the effectiveness of good work as many as 24 people (80.0%) and less as many as 6 people (20.0%), it is recommended that Medan Adventist Hospital provide SOPs related to electronic medical records and carry out routine system maintenance to prevent errors.